New species of Euplocania Enderlein (Psocodea: ‘Psocoptera’: Psocomorpha), in three species groups, from Colombia and Ecuador - Obando, Ranulfo González; Aldrete, Alfonso N. García; Carrejo, Nancy; Panche, Jeferson (Zootaxa, 2018)
Eight species of Euplocania from Colombia, in species groups Bonaverensis, Enderleini and Patinoi, are here described and illustrated. They raise to 40 the number of species described in the genus, 27 of which are found in Colombia. Of the Colombian species, one is shared with Ecuador and one is shared with Brazil and Peru. A key to identify the males of the species here described is included.